The road to optimal acceleration of Dixon imaging and quantitative T2-mapping in the ankle using compressed sensing and parallel imaging. Issue 132 (November 2020) - Baur, O.L.; Den Harder, J.M.; Hemke, R.; Farid, F. Mojtahedi; Smithuis, F.; De Weerdt, E.; Nederveen, A.J.; Maas, M.
Highlights: A TSE-Dixon protocol of the ankle can be accelerated by 45 % with CS-SENSE. T2-mapping sequences can be accelerated by 30 % using CS-SENSE. A structured method to find optimal acceleration might lead to higher acceleration factors. Abstract: Objective: This study aimed to find the optimal acceleration factor achievable with CS-SENSE for a clinical ankle protocol while maintaining comparable image quality. Methods: We explored the optimal acceleration achievable with factor CS-SENSE, for an ankle protocol with T2-weighted, PD-weighted TSE-Dixon (coronal, axial and sagittal) and T2-mapping (sagittal) sequences, on a 3 T MRI-scanner. This study contained three steps: (1) phantom test, (2) pilot test on healthy volunteers, (3) anatomical assessment on a cohort of healthy volunteers and a quantitative analysis. CS-SENSE images (acceleration factors between 2.0× and 12.0×) were compared to reference SENSE images (acceleration factor 2.0×). Three blinded radiologists evaluated the image quality and provided an anatomical assessment using a five-point Likert scale of 25 anatomical regions. Results: The total acquisition time of the TSE-Dixon sequence was reduced by 45 % from 13′38″ to 7′37″ (acceleration factor between 3.6× and 4.0×), the T2-mapping scan time was reduced by 31 % from 5′28″ to 3′47″ (acceleration factor of 3.0×), while maintaining comparable image quality. The results from the anatomical assessment of SENSE 2.0× versus CS-SENSE 3.6× were comparable in 88.7 % as shown by the 5-point Likert scale measurements. The T2-relaxation measurements had a good correlation of ρ = 0.7 between SENSE and CS-SENSE. Conclusion: We found an optimum acceleration factor with CS-SENSE between 3.6× and 4.0× for TSE-Dixon and 3.0× for T2-mapping sequences in a clinical MR imaging protocol of the ankle. The total scan time was reduced by 41 % while maintaining adequate image quality.